2019
DOI: 10.1183/23120541.00147-2018
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary exacerbations in patients with primary ciliary dyskinesia: an expert consensus definition for use in clinical trials

Abstract: Pulmonary exacerbations are a cause of significant morbidity in patients with primary ciliary dyskinesia (PCD) and are frequently used as an outcome measure in clinical research into chronic lung diseases. So far, there has been no consensus on the definition of pulmonary exacerbations in PCD.30 multidisciplinary experts and patients developed a consensus definition for children and adults with PCD. Following a systematic review, the panel used a modified Delphi process with a combination of face-to-face meeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 43 publications
0
39
0
1
Order By: Relevance
“…The exacerbations in PCD, defined as an acute increase in respiratory symptoms [14], are predictors of severity of disease and poor quality of life [10] and negatively impact on lung function, as bacterial infections are associated with morbidity and mortality in these patients [13]. It was reported that about 25% of children with PCD fail to recover to baseline lung function within 3 months following a pulmonary exacerbation treated with intravenous antibiotics and may never regain pre-exacerbation spirometry [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The exacerbations in PCD, defined as an acute increase in respiratory symptoms [14], are predictors of severity of disease and poor quality of life [10] and negatively impact on lung function, as bacterial infections are associated with morbidity and mortality in these patients [13]. It was reported that about 25% of children with PCD fail to recover to baseline lung function within 3 months following a pulmonary exacerbation treated with intravenous antibiotics and may never regain pre-exacerbation spirometry [15].…”
Section: Discussionmentioning
confidence: 99%
“…We considered the definition of exacerbation in PCD as indicated by expert consensus (14). As the median of exacerbations was 2 per year prior to the analysis in our patients, we classified patients in two groups: Low-EXAC: < 2/year and High-EXAC ≥2/year.…”
Section: Number Of Exacerbationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, this work did not examine the effect of pulmonary exacerbations on HRQoL in PCD as a formal definition for pulmonary exacerbation in PCD was not available at the beginning of this study. Since 2019, an expert consensus statement has been proposed for PCD [36] and future studies are expected to focus on the responsiveness of QOL-PCD to pulmonary exacerbations in PCD.…”
Section: Discussionmentioning
confidence: 99%
“…Primary ciliary dyskinesia (PCD) is an inherited heterogeneous motile ciliopathy, in which respiratory cilia are stationary, or beat in a dyskinetic manner, leading to significant sinopulmonary disease . Currently, there is no single gold standard test which will diagnose every patient with PCD, and international guidelines recommend a panel of a variety of tests to diagnose PCD .…”
Section: Introductionmentioning
confidence: 99%